The Kabbalistic Culture of Eighteenth-Century Prague : Ezekiel Landau (the 'Noda Biyehudah') and His Contemporaries. - Flatto, Sharon (Littman Library of Jewish Civilization, The, 2015)
A comprehensive portrayal of rabbinic culture in eighteenth-century Prague highlighting the surprising centrality of kabbalah in one of the main centres of European Jewry.
Description based upon print version of record.
Keywords: Judaism -- Czech Republic -- Prague -- History.; Cabala -- Czech Republic -- Prague -- History.; Mysticism -- Judaism -- History.; Jews -- Czech Republic -- Prague -- History.; Prague (Czech Republic) -- History.; Judaïsme -- République tchèque -- Prague -- Histoire.; Kabbale -- République tchèque -- Prague -- Histoire.; Mysticisme -- Judaïsme -- Histoire.; Juifs -- République tchèque -- Prague -- Histoire.; Mysticism -- Judaism; Judaism; Jews; Cabala; Czech Republic -- Prague; History